Differences in Executive Function Between Batterers and Other Criminals. Issue 5 (19th October 2016) - Bueso-Izquierdo, Natalia; Hidalgo-Ruzzante, Natalia; Daugherty, Julia C.; Burneo-Garcés, Carlos; Pérez-García, Miguel
ABSTRACT: While the neuropsychological profile of criminals has been studied extensively, there is little neuropsychological research on batterers, and there is no study that compares both groups. The main objective of the present study was to examine executive functioning of male batterers, in comparison with other criminals, using a comprehensive executive functioning battery. Data were obtained from a sample of 28 men sentenced for intimate partner violence (IPV), and 35 criminals sentenced for other crimes. Results showed that batterers were more inflexible, but less impulsive than other criminals. These results provide a preliminary understanding of executive functioning in IPV batterers.